Diana : Her True Story - Morton, Andrew (London Michael O'Mara Books, 1997)
Originally published in 1992, this biography was produced with the full co-operation and input of the Princess. Following the tragic and sudden death of the Princess in August 1997, the book has been fully revised to contain new material and photographs and is designed to stand as a tribute to her.
Include Illustrations and Index.
Diana's True Story.
Keywords: Great Britain -- Diana, Princess of Wales, 1961-1997 -- Princesses